Towards Creative Software Blending: Computational Infrastructure and Use Cases - Martinc, Matej; Žnidaršič, Martin; Lavrač, Nada; Pollak, Senja (Informatica, 2018)
Numerous visual programming platforms support the generation, execution and reuse of constructed scientic workows. However, there has been little effort devoted to building creative software blending systems, capable of composing novel workows by autonomously combining individual software components or even entire workows originally designed for solving tasks in different research elds. Based on the review of relevant computational creativity research and of contemporary web platforms for workow construction, this paper denes the desired functionality of a software blending system. Considering the required autonomy of the system and the workow complexity limitations, we investigate the necessary conditions for the implementation of a creative blending system within the existing visual programming platforms.